The Reaction of Peshkawtn Newspaper against the Iraqi Government and Its Associations during Its Kingdom (1921-1958) - Hewa khalel Othman; Muhammad Abdulla kakassur (QALAAI ZANIST JOURNAL, 2021)
Journalism plays a huge role in serving history. After the First World War (1914-1918), Iraq was under British occupation, The UK created a country by this name as the British colony intended to include Kurdistan, but it encountered many challenges and obstacles. Therefore, they were committed to serving their own interests while trying to sympathize with the Kurds. The UK has implemented some reforms, bringing the printing association to Kurdistan where Newspapers were published and printed in Kurdish. One of the newspapers playing a major role in the History of Journalism was (Peshkawtn Newspaper). It was continuously published from 1920 to 1922. Even though the newspaper used to be published under the British leadership in Sulaimany city, it has made many contributions to Kurdish Journalism. Thus, we might say that the Newspaper (Peshkawtn) was not published under the Kurdish leadership, and its main goal was not to serve the Kurds, but it had played its part in advancing and enriching our Kurdish Journalism in many ways.